2006
DOI: 10.1162/jocn.2006.18.7.1133
|View full text |Cite
|
Sign up to set email alerts
|

Prefrontal Engagement during Source Memory Retrieval Depends on the Prior Encoding Task

Abstract: The prefrontal cortex is strongly engaged by some, but not all, episodic memory tests. Prior work has shown that source recognition tests-those that require memory for conjunctions of studied attributes-yield deficient performance in patients with prefrontal damage and greater prefrontal activity in healthy subjects, as compared to simple recognition tests. Here, we tested the hypothesis that there is no intrinsic relationship between the prefrontal cortex and source memory, but that the prefrontal cortex is e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
41
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 53 publications
8
41
0
Order By: Relevance
“…Light and Berger (1976) found that when subjects were instructed that they would be tested for their memory of words and their fonts, word/font conjunctions were better remembered than word/color conjunctions, and vice versa when subjects were instructed that the word/color relationships were critical. In a previous experiment closely related to the current design, we have shown that the nature of the encoding task is important even under intentional encoding instructions (Kuo & Van Petten, 2006). In that experiment, participants were always aware that the memory test would require judgments about drawings and their colors.…”
mentioning
confidence: 78%
See 2 more Smart Citations
“…Light and Berger (1976) found that when subjects were instructed that they would be tested for their memory of words and their fonts, word/font conjunctions were better remembered than word/color conjunctions, and vice versa when subjects were instructed that the word/color relationships were critical. In a previous experiment closely related to the current design, we have shown that the nature of the encoding task is important even under intentional encoding instructions (Kuo & Van Petten, 2006). In that experiment, participants were always aware that the memory test would require judgments about drawings and their colors.…”
mentioning
confidence: 78%
“…The relationship between PFC and spatiotemporal source memory was corroborated in healthy young adults via event-related potentials (ERPs) in list-discrimination and spatial source tests (Trott, Friedman, & Ritter, 1997;Van Petten, Senkfor, & Newberg, 2000). On the other hand, a number of ERP studies have also demonstrated engagement of PFC during source tests that tap conjunctions of perceptual attributes that might be considered "intra-item", such as wordvoice and object-color pairings (Friedman, Cycowicz, & Bersick, 2005;Senkfor & Van Petten, 1998;Kuo & Van Petten, 2006;Wilding, Doyle, & Rugg, 1995 Segal, & Hart, 2003;Suzuki et al, 2002), perceptual judgments (Fan, Snodgrass, & Bilder, 2003;Ranganath, Heller, & Wilding, 2007;Ranganath, Johnson, & D'Esposito, 2000;Raye, Johnson, Mitchell, & Nolde, 2000), and judgments about the encoding task that accompanied a stimulus (Dobbins, Foley, Schacter, & Wagner, 2002;Dobbins & Han, 2006;Dobbins, Rice, Wagner, & Schacter, 2003). However, these observations of prefrontal activity across intraitem and extra-item source tests have little to say about the possibility that some varieties of source information place greater retrieval demands on PFC than others.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…During the late latency range of 800-1300 ms, ERPs elicited by new objects showed only small, and statistically nonsignificant differences between the item and source memory tests. The greater impact of test type on hits than correct rejections resulted in a larger old/new difference at prefrontal sites during the source than item test, albeit smaller than in our other work using perceptual source attributes of voice, location, and color (Senkfor & Van Petten, 1998; Van Petten et al, 2000; Kuo & Van Petten, 2006). Late prefrontal effects of test-type are thus different in nature than other test-type effects that influence both studied and unstudied items (and for clarity we suggest that only the latter should be called "retrieval orientation" effects).…”
Section: Orienting Retrieval To Item Versus Source Informationmentioning
confidence: 52%
“…Considering the large number of stimuli to be remembered, this level of accuracy is substantially better than previous studies in which the source discrimination based on only one perceptual attribute of the stimulus (such as voice, spatial location, or color; Senkfor and Van Petten, 1998; Van Petten et al, 2000; Kuo & Van Petten, 2006). Despite a number of quantitative similarities (such as the high degree of self-initiation), the Perform and Cost conditions used here were designed to be maximally distinct from one another in qualitative properties, so that multiple attributes of the encoding episode could provide source-differentiating information, including engagement of the motor system, tactile and proprioceptive feedback from handling the object, presence versus absence of visual motion, and the cognitive operations engaged by cost estimation but not action (which could include comparisons to other objects, retrieval of autobiographical memories for purchasing a similar object, etc.).…”
Section: The Efficacy Of Enactment Versus Conceptual Encodingmentioning
confidence: 77%